Mitigating rapid release of nitrate from rejected sago starch-coated urea and uncoated urea - Omar, Latifah Binti; Primus, Walter Charles; Kasim, Susilawati Binti; Kavitha, Rajan; Ahmed, Osumanu Haruna (Malaysian Society of Soil Science, 2024)
Urea is the most widely used nitrogen (N) fertilizer as it has a high N content (46%), is inexpensive, easily available, and can be conveniently stored. However, the high water-solubility and rapid hydrolysis of urea in the soil leads to much N loss. Rejected sago starch (RSS) was used to coat urea to prevent rapid release of N. A soil leaching experiment was conducted over 30 days to determine the effectiveness of RSS-coated urea in retaining soil N availability in the form of exchangeable NH4 + and available NO3 - compared with uncoated urea. The soil used in the leaching experiment was Bekenu Series (Sandy loam, Typic Paleudults). This study compared seven different treatments: soil alone (S), 5 g of uncoated urea (U), 5 g of 2% RSS-coated urea (CU1), 5 g of 3% RSS-coated urea (CU2), 5 g of 4% RSS-coated urea (CU3), 5 g of 5% RSS-coated urea (CU4), and 5 g of 6% RSS-coated urea (CU5). The RSS-coated urea (CU1, CU2, CU3, and CU4) significantly reduced N leaching due to the coating on the urea that serves as a barrier which slows down the conversion of N into NH4 + and NO3 −. Gradual released of N helps in retaining more soil exchangeable NH4 + in all RSS-coated urea than uncoated urea. Optimize use of RSS-coated urea in CU1 (2% of RSS) did not only mitigates NO3 - leaching, but it is also increasing soil TOM, TOC, total N, soil exchangeable NH4 +, and available NO3 - although all the RSS-coated urea has minimal effects on soil pH.